Fatten, butchering and lard and flash qualities of pigs of different areas of productivity - Бірта, Г. О.; Бургу, Ю. Г. (Scientific Progress & Innovations, 2012)
To be succeeded in commercial output of meat in our country nowadays (and aforetime as well) it is very important to pay attention to intensification of pig farming industry mainly pointed at increasing the actual productivity of animals, reducing cost price and improvement of the pork quality. Of all effective techniques that contribute to the high pigs productivity, a special place belongs to implementation of science-based farming system, which is based on the maximum use of available in each region breeds, specialized types and lines, precise connection between breeding and commercial farms, the rational usage of heterosis phenomenon and provision optimal conditions in animal feeding and keeping as well.